Elder’s decision of moving to pondok living arrangement in Malaysia - Nor Aisah Areff,; Novel Lyndon, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Studies on elders decision to move to different congregated living arrangements in the developed nations have been conducted extensively. As the elders’ view is perennially significant in qualitative approach, this article emphasises the reasons of elders’ move to Jeram Pondok, an alternative congregated living arrangement which has been established for the dissemination of Islam through teaching and learning. Therefore, an abductive research strategy centred on idealist ontology and social constructionist epistemology was engaged to explain their social reality. The meanings constructed by them as social actors were interpreted through the employment of in-depth interviews with 20 elderly informants. The findings yielded three main themes of information and interest in pondok, decision maker and reasons of move with five essential sub-themes of religion, relationships with family members and friends, forging new relationship, autonomy and death in understanding the meanings attached to their everyday experience. Lastly, understanding the elders’ decision to move to pondok would present a better explanation of their needs based on their socio-cultural reality for planning and implementation of future policies relevant to them.